Steel structural part surface repairing composite putty and preparation method thereof
By using a combination of modified unsaturated polyester resin and admixture in atomic ash, the adhesion and corrosion protection problems caused by shrinkage after curing are solved, and better adhesion and long-term corrosion protection are achieved.
Patent Information
- Application Number
- CN202411739827.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing unsaturated polyester resin causes atomic ash to shrink after curing, which can easily cause defects such as shrinkage deformation and warping, and in severe cases, it may even affect the adhesion of atomic ash to the substrate.
Modified unsaturated polyester resin is used as the base material for atomic ash. By adding admixtures during the polymerization process, the double bonds of the admixtures undergo a Diels-Alder reaction with the double bonds of the unsaturated polyester molecular chain. The modified unsaturated polyester resin reduces the shrinkage rate and improves adhesion during the curing process.
After curing, the modified unsaturated polyester resin reduces the shrinkage rate, improves the adhesion and delicate construction properties of atomic ash, enhances the barrier effect on corrosive media, and achieves long-term anti-corrosion performance.
Smart Images

Figure BDA0005162380490000121 
Figure BDA0005162380490000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, and in particular to a composite putty for repairing the surface of a steel structure and a preparation method thereof. Background Art
[0002] Putty, also known as unsaturated polyester resin putty, is a kind of embedding material that has developed rapidly in the world in recent decades. Putty is a paste-like composite material, which consists of a main agent (mixed and ground unsaturated polyester resin, pigments, fillers, accelerators, etc.) and a curing agent (organic peroxides such as cyclohexanone peroxide and methyl ethyl ketone peroxide). Putty has the characteristics of fast curing, easy grinding, strong adhesion and no cracking. It is mainly used for filling and leveling of base material coating to meet the requirements of flatness and smoothness of the base material surface before topcoat. It is widely used as a filling material in the automobile manufacturing, machinery, vehicle repair and other industries.
[0003] As the base material of putty, unsaturated polyester resin has a great influence on the relevant properties of putty. When unsaturated polyester resin is cured, the double bonds are opened and cross-linked to form spatial network macromolecules. After the double bonds are cross-linked, the Van der Waals force becomes a covalent bond, which will inevitably shorten the distance between the molecular chains, resulting in a large shrinkage rate of the putty. Moreover, after curing, the number of disordered molecular chains in the system decreases, and the free volume is reduced, which will also cause the shrinkage of the putty. The unsaturated polyester resin used in the prior art generally has a curing volume shrinkage of 5-7%, which is easy to cause defects such as shrinkage deformation and warping. In severe cases, it even affects the adhesion of the putty to the substrate. Summary of the invention
[0004] The purpose of the present invention is to provide a composite putty for repairing the surface of a steel structure and a preparation method thereof, so as to solve the following technical problems:
[0005] The existing unsaturated polyester resin causes the putty to shrink after curing, which easily causes defects such as shrinkage deformation and warping. In severe cases, it even affects the adhesion of the putty to the substrate.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing composite putty for repairing the surface of a steel structure comprises the following steps: mixing a main agent and a curing agent to obtain putty;
[0008] The main agent includes the following raw materials in parts by weight: 40-50 parts of modified unsaturated polyester, 1-3 parts of accelerator, 1-2 parts of fumed silica, and 40-50 parts of filler;
[0009] The preparation method of modified unsaturated polyester comprises the following steps:
[0010] S1: In a nitrogen atmosphere, dicyclopentadiene, maleic anhydride, diethylene glycol and phosphoric acid are added to a reaction kettle with a reflux device and dispersed evenly, the temperature is controlled at 100-110°C, and the reaction is kept warm for 0.5-1h, deionized water is added, the temperature is controlled at 120-130°C, and the reaction is kept warm for 2-4h to obtain a reaction solution;
[0011] S2: In a nitrogen atmosphere, the reaction liquid, phthalic anhydride, diethylene glycol, 1,2-propylene glycol, and hydroquinone component 1 are added to a reactor with a distillation device and dispersed evenly, and a three-stage temperature increase reaction is carried out until the acid value drops to 60-70 mg / g, an additive is added, the temperature is controlled at 190-200°C, and the temperature is kept to react until the acid value drops to 30-40 mg / g, the temperature is controlled at 150-160°C, and the hydroquinone component 2 is added, the temperature is controlled at 90-100°C, styrene is added, stirred evenly, and cooled to obtain a modified unsaturated polyester;
[0012] The additive is obtained by esterifying castor oil with maleic anhydride and then reacting with gamma-aminopropyltriethoxysilane.
[0013] Preferably, the addition ratio of dicyclopentadiene, maleic anhydride, diethylene glycol, phosphoric acid and deionized water in S1 is 100 g: 92-122 g: 24-32 g: 0.4-0.5 g: 15-20 mL.
[0014] Preferably, the hydroquinone component one and the hydroquinone component two in S2 are both hydroquinone; the addition ratio of the reaction solution, phthalic anhydride, diethylene glycol, 1,2-propylene glycol, hydroquinone component one, admixture, hydroquinone component two, and styrene is 100g: 30-40g: 3.5-7g: 20.2-27.8g: 0.01-0.02g: 10-15g: 0.01-0.02g: 45-55g.
[0015] Preferably, the preparation method of the admixture comprises the following steps:
[0016] A1: Add castor oil and maleic anhydride into reactor A and disperse them evenly. Control the temperature at 100-110°C and keep the temperature for 3-6 hours to obtain carboxylated castor oil.
[0017] A2: Add carboxylated castor oil, γ-aminopropyltriethoxysilane and triethylamine into reactor B and disperse them evenly. Control the temperature at 70-80°C and keep the temperature for reaction for 1-3 hours to obtain an admixture.
[0018] Preferably, the addition ratio of castor oil to maleic anhydride in A1 is 9g:1-3g.
[0019] Preferably, the addition ratio of carboxylated castor oil, γ-aminopropyltriethoxysilane and triethylamine in A2 is 10g: 2-3g: 0.2-0.3g.
[0020] Preferably, the specific procedure of the three-stage temperature increase reaction in S2 is: first increase the temperature to 150-160°C and keep warm for 1-3 hours; then increase the temperature to 165-170°C and keep warm for 0.5-1 hour; finally increase the temperature to 175-185°C and react until the acid value drops to 60-70 mg / g.
[0021] Preferably, the accelerator is a mixture of a cobalt drier and dimethylaniline in a mass ratio of 0.1-0.5:1.5-2.5, and the cobalt drier is cobalt cyclohexaneate or cobalt isooctanoate;
[0022] The filler is obtained by mixing talcum powder, barium sulfate and titanium dioxide in a mass ratio of 35-45:1-10:2-5.
[0023] Preferably, the mass ratio of the main agent to the curing agent in the putty is 100:2-3.
[0024] Preferably, the curing agent comprises the following raw materials in percentage by weight: 50-60% peroxide initiator, 30-49% plasticizer, 1% pigment, and the sum of the percentages of the raw materials is 100%.
[0025] Preferably, the plasticizer is any one of a diformic acid ester plasticizer, a polyester plasticizer, a phosphate ester plasticizer, a fatty acid ester plasticizer, and an epoxy ester plasticizer;
[0026] The peroxide is any one of cumene hydroperoxide, di-tert-butyl peroxide, dicumyl peroxide, benzoyl peroxide, dilauroyl peroxide, cyclohexanone peroxide, and methyl ethyl ketone peroxide;
[0027] The pigment is at least one of an organic pigment and an inorganic pigment.
[0028] Preferably, the organic pigment is any one of phthalocyanine pigments and azo pigments; the non-pigmented pigment is any one of white carbon black, titanium dioxide and chrome yellow.
[0029] A composite putty for repairing the surface of a steel structure is prepared by any one of the above preparation methods.
[0030] Beneficial effects of the present invention:
[0031] (1) The present application first uses maleic anhydride and castor oil to prepare carboxylated castor oil containing carbon-carbon double bonds, and uses γ-aminopropyl triethoxysilane to react with carboxylated castor oil to obtain an admixture. The present application then uses maleic acid generated by the reaction of maleic anhydride and water to react with dicyclopentadiene to undergo an acid-catalyzed addition reaction to generate dicyclopentadiene maleic acid monoester, and finally uses dicyclopentadiene maleic acid monoester, diol, and diacid to polymerize to obtain unsaturated polyester, and adds an admixture during the polymerization process, and the double bonds of the admixture react with the double bonds of the unsaturated polyester molecular chain to undergo a Diels-Alder reaction to obtain a modified unsaturated polyester. The modified unsaturated polyester prepared in the present application is added to the main agent as the base material of the putty. The putty prepared in the present application has good air-drying properties, excellent polishability, strong adhesion, as well as good flexibility, impact resistance, scratch resistance, storage stability, etc.
[0032] The modified unsaturated polyester resin of the present application is used as the base material of the putty. When the substrate is a metal material, after the putty is coated, the resin and the substrate form a double electric layer, generating an interface contact potential, thereby improving the adhesion performance of the putty on the substrate; the silane coupling agent grafted on the unsaturated polyester molecular chain migrates to the interface of the metal substrate, and in addition to generating hydrogen bonds or condensing into -SiOM covalent bonds (M is the substrate), the silanol groups between the silane molecules condense and aggregate to form a network structure film covering the surface of the substrate, and its bond energy is much greater than the interfacial force from the van der Waals attraction, which not only shows good adhesion to the substrate interface; but also the silanol groups of the silane coupling agent can be hydrogen bonded to each other in the flowing resin matrix, which greatly improves the dispersibility of the filler in the resin and makes the construction of the putty fine. The components of the putty material of the present application are balanced by adding additives to adjust the cohesive force of the resin itself and the adhesion between the putty and the substrate, effectively reducing the gap between the organic coating and the metal substrate, effectively reducing the shrinkage rate of the putty during the curing process, improving the adhesion between the putty and the metal substrate, and improving the material's barrier effect on corrosive media. This solves the problem in the prior art that when zinc powder is added as an electrochemical anti-corrosion to achieve anti-corrosion performance at a low potential, the zinc powder in the putty will be consumed during the corrosion process and can only achieve short-term anti-corrosion. The putty prepared in the present application achieves long-term anti-corrosion performance.
[0033] (2) A peroxide initiator is added to the curing agent of the present application. The initiator decomposes to generate free radicals, which promotes the cross-linking and curing of the unsaturated polyester resin at room temperature; an accelerator is added to the present application and used in combination with the initiator. The accelerator is not only beneficial for accelerating the decomposition of the peroxide under room temperature conditions, but also has a reducing property. It forms an oxidation-reduction reaction system with the peroxide initiator to initiate polymerization, promote the initiation effect in the polyester resin, and make the polyester cure at room temperature; dimethylaniline is added to the accelerator of the present application. The reaction of dimethylaniline with the peroxide initiator accelerates the decomposition of the peroxide group and has a significant promoting effect. DETAILED DESCRIPTION
[0034] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] The preparation method of the admixture of embodiment 1 comprises the following steps:
[0036] A1: 18 g of castor oil (hydroxyl value: 168 mgKOH / g) and 6 g of maleic anhydride were added into reactor A and dispersed evenly. The temperature was controlled at 100°C and the reaction was kept at this temperature for 6 hours to obtain carboxylated castor oil.
[0037] A2: Add 20g of carboxylated castor oil, 5g of γ-aminopropyltriethoxysilane and 0.6g of triethylamine into reactor B and disperse them evenly. Control the temperature to 70°C and keep the reaction warm for 3h to obtain an admixture.
[0038] Embodiment 2 The preparation method of modified unsaturated polyester comprises the following steps:
[0039] S1: In a nitrogen atmosphere, 100 g of dicyclopentadiene, 92 g of maleic anhydride, 24 g of diethylene glycol, and 0.4 g of phosphoric acid were added to a reactor with a reflux device and dispersed evenly, the temperature was controlled at 100°C, and the reaction was kept warm for 0.5 h. 15 mL of deionized water was added, the temperature was controlled at 120°C, and the reaction was kept warm for 2 h to obtain a reaction solution;
[0040] S2: In a nitrogen atmosphere, 100 g of the reaction solution, 30 g of phthalic anhydride, 3.5 g of diethylene glycol, 20.2 g of 1,2-propylene glycol, and 0.01 g of hydroquinone are added to a reactor with a distillation device and dispersed evenly. The temperature is first raised to 150°C and kept warm for 1 hour; then raised to 165°C and kept warm for 0.5 hour; finally raised to 175°C and reacted until the acid value dropped to 70 mg / g, 15 g of the admixture prepared in Example 1 is added, the temperature is controlled at 190°C, the reaction is kept warm until the acid value drops to 30 mg / g, the temperature is controlled at 150°C, 0.01 g of hydroquinone is added, the temperature is controlled at 90°C, 45 g of styrene is added, stirred evenly and cooled to obtain a modified unsaturated polyester.
[0041] Embodiment 3 The preparation method of modified unsaturated polyester comprises the following steps:
[0042] S1: In a nitrogen atmosphere, 100 g of dicyclopentadiene, 102 g of maleic anhydride, 28 g of diethylene glycol, and 0.4 g of phosphoric acid were added to a reactor with a reflux device and dispersed evenly, the temperature was controlled at 105°C, and the reaction was kept warm for 0.5 h. 17 mL of deionized water was added, the temperature was controlled at 125°C, and the reaction was kept warm for 3 h to obtain a reaction solution;
[0043] S2: In a nitrogen atmosphere, 100 g of the reaction solution, 35 g of phthalic anhydride, 5.5 g of diethylene glycol, 25.2 g of 1,2-propylene glycol, and 0.01 g of hydroquinone are added to a reactor with a distillation device and dispersed evenly. The temperature is first raised to 155°C and kept warm for 2 h; then raised to 165°C and kept warm for 0.5 h; finally raised to 180°C and reacted until the acid value dropped to 70 mg / g, 15 g of the admixture prepared in Example 1 is added, the temperature is controlled at 195°C, and the reaction is kept warm until the acid value drops to 30 mg / g, the temperature is controlled at 155°C, 0.01 g of hydroquinone is added, the temperature is controlled at 95°C, 50 g of styrene is added, stirred evenly and cooled to obtain a modified unsaturated polyester.
[0044] Embodiment 4 The preparation method of modified unsaturated polyester comprises the following steps:
[0045] S1: In a nitrogen atmosphere, 100 g of dicyclopentadiene, 122 g of maleic anhydride, 32 g of diethylene glycol, and 0.4 g of phosphoric acid were added to a reactor with a reflux device and dispersed evenly, the temperature was controlled at 110°C, and the reaction was kept warm for 0.5 h. 20 mL of deionized water was added, the temperature was controlled at 130°C, and the reaction was kept warm for 4 h to obtain a reaction solution;
[0046] S2: In a nitrogen atmosphere, 100 g of the reaction solution, 40 g of phthalic anhydride, 7 g of diethylene glycol, 27.8 g of 1,2-propylene glycol, and 0.01 g of hydroquinone are added to a reactor with a distillation device and dispersed evenly. The temperature is first raised to 160°C and kept warm for 3 h; then raised to 170°C and kept warm for 1 h; finally raised to 185°C and reacted until the acid value dropped to 70 mg / g, 15 g of the additive prepared in Example 1 is added, the temperature is controlled at 200°C, and the reaction is kept warm until the acid value drops to 30 mg / g, the temperature is controlled at 160°C, 0.01 g of hydroquinone is added, the temperature is controlled at 100°C, 55 g of styrene is added, stirred evenly and cooled to obtain a modified unsaturated polyester.
[0047] Embodiment 5 A method for preparing composite putty for surface repair of steel structure parts comprises the following steps:
[0048] B1: 50 g of the modified unsaturated polyester prepared in Example 2, 0.5 g of cobalt cyclohexaneate, 1.5 g of dimethylaniline, 1 g of fumed silica, 35 g of talc, 3 g of barium sulfate, and 2 g of titanium dioxide were stirred evenly, and vacuumed to obtain a main agent;
[0049] B2: 6 g of cyclohexanone peroxide, 3.9 g of dibutyl phthalate, and 0.1 g of white carbon black were blended to obtain a curing agent;
[0050] B3: Mix 50g of the main agent and 1g of the curing agent to obtain putty.
[0051] Embodiment 6 A method for preparing composite putty for surface repair of steel structure parts comprises the following steps:
[0052] B1: 50 g of the modified unsaturated polyester prepared in Example 3, 0.5 g of cobalt cyclohexaneate, 1.5 g of dimethylaniline, 1 g of fumed silica, 35 g of talc, 3 g of barium sulfate, and 2 g of titanium dioxide were stirred evenly, and vacuumed to obtain a main agent;
[0053] B2: 6 g of cyclohexanone peroxide, 3.9 g of dibutyl phthalate, and 0.1 g of white carbon black were blended to obtain a curing agent;
[0054] B3: Mix 50g of the main agent and 1g of the curing agent to obtain putty.
[0055] Embodiment 7 A method for preparing composite putty for repairing the surface of a steel structure comprises the following steps:
[0056] B1: 50 g of the modified unsaturated polyester prepared in Example 4, 0.5 g of cobalt cyclohexaneate, 1.5 g of dimethylaniline, 1 g of fumed silica, 35 g of talc, 3 g of barium sulfate, and 2 g of titanium dioxide were stirred evenly, and vacuumed to obtain a main agent;
[0057] B2: 6 g of cyclohexanone peroxide, 3.9 g of dibutyl phthalate, and 0.1 g of white carbon black were blended to obtain a curing agent;
[0058] B3: Mix 50g of the main agent and 1g of the curing agent to obtain putty.
[0059] The preparation method of the admixture of Comparative Example 1 comprises the following steps:
[0060] 18 g of castor oil (hydroxyl value: 168 mgKOH / g) and 6 g of maleic anhydride were added into reactor A and dispersed evenly. The temperature was controlled at 100° C. and the reaction was kept warm for 6 hours to obtain an admixture.
[0061] The preparation method of the admixture of Comparative Example 2 comprises the following steps:
[0062] Add 6 g of maleic anhydride, 5 g of γ-aminopropyltriethoxysilane, 10 mL of N,N-dimethylformamide and 10 mL of deionized water into reactor A and disperse them evenly. Control the temperature at 70°C and keep the reaction warm for 3 h. Rotary evaporate to remove the solvent to obtain an admixture.
[0063] The preparation method of the admixture of Comparative Example 3 comprises the following steps:
[0064] A1: 6 g of maleic anhydride, 5 g of γ-aminopropyltriethoxysilane, 10 mL of N,N-dimethylformamide, and 10 mL of deionized water were added to reactor A and dispersed evenly. The temperature was controlled at 70°C and the reaction was kept warm for 3 h. The solvent was removed by rotary evaporation to obtain carboxylated silane.
[0065] A2: The carboxylated silane prepared in step A1 was blended with 18 g of castor oil (hydroxyl value: 168 mgKOH / g) to obtain an admixture.
[0066] Comparative Example 4 The preparation method of modified unsaturated polyester comprises the following steps:
[0067] S1: In a nitrogen atmosphere, 100 g of dicyclopentadiene, 102 g of maleic anhydride, 28 g of diethylene glycol, and 0.4 g of phosphoric acid were added to a reactor with a reflux device and dispersed evenly, the temperature was controlled at 105°C, and the reaction was kept warm for 0.5 h. 17 mL of deionized water was added, the temperature was controlled at 125°C, and the reaction was kept warm for 3 h to obtain a reaction solution;
[0068] S2: In a nitrogen atmosphere, 100 g of the reaction solution, 35 g of phthalic anhydride, 5.5 g of diethylene glycol, 25.2 g of 1,2-propylene glycol, and 0.01 g of hydroquinone are added to a reactor with a distillation device and dispersed evenly. The temperature is first raised to 155°C and kept warm for 2 hours; then the temperature is raised to 165°C and kept warm for 0.5 hours; finally the temperature is raised to 180°C and reacted until the acid value drops to 70 mg / g, 15 g of the additive prepared in Comparative Example 1 is added, the temperature is controlled at 195°C, the temperature is kept warm and reacted until the acid value drops to 30 mg / g, the temperature is controlled at 155°C, 0.01 g of hydroquinone is added, the temperature is controlled at 95°C, 50 g of styrene is added, stirred evenly and cooled to obtain a modified unsaturated polyester.
[0069] Comparative Example 5 The preparation method of modified unsaturated polyester comprises the following steps:
[0070] S1: In a nitrogen atmosphere, 100 g of dicyclopentadiene, 102 g of maleic anhydride, 28 g of diethylene glycol, and 0.4 g of phosphoric acid were added to a reactor with a reflux device and dispersed evenly, the temperature was controlled at 105°C, and the reaction was kept warm for 0.5 h. 17 mL of deionized water was added, the temperature was controlled at 125°C, and the reaction was kept warm for 3 h to obtain a reaction solution;
[0071] S2: In a nitrogen atmosphere, 100 g of the reaction solution, 35 g of phthalic anhydride, 5.5 g of diethylene glycol, 25.2 g of 1,2-propylene glycol and 0.01 g of hydroquinone are added to a reactor with a distillation device and dispersed evenly. The temperature is first raised to 155°C and kept warm for 2 hours; then the temperature is raised to 165°C and kept warm for 0.5 hours; finally the temperature is raised to 180°C and reacted until the acid value drops to 70 mg / g, 15 g of the additive prepared in Comparative Example 2 is added, the temperature is controlled at 195°C, the temperature is kept warm and reacted until the acid value drops to 30 mg / g, the temperature is controlled at 155°C, 0.01 g of hydroquinone is added, the temperature is controlled at 95°C, 50 g of styrene is added, the mixture is stirred evenly and cooled to obtain a modified unsaturated polyester.
[0072] Comparative Example 6 The preparation method of modified unsaturated polyester comprises the following steps:
[0073] S1: In a nitrogen atmosphere, 100 g of dicyclopentadiene, 102 g of maleic anhydride, 28 g of diethylene glycol, and 0.4 g of phosphoric acid were added to a reactor with a reflux device and dispersed evenly, the temperature was controlled at 105°C, and the reaction was kept warm for 0.5 h. 17 mL of deionized water was added, the temperature was controlled at 125°C, and the reaction was kept warm for 3 h to obtain a reaction solution;
[0074] S2: In a nitrogen atmosphere, 100g of the reaction solution, 35g of phthalic anhydride, 5.5g of diethylene glycol, 25.2g of 1,2-propylene glycol and 0.01g of hydroquinone are added to a reactor with a distillation device and dispersed evenly. First, the temperature is raised to 155°C and kept warm for 2h; then the temperature is raised to 165°C and kept warm for 2h. The castor oil prepared in Comparative Example 3 is controlled at 195°C and kept warm until the acid value drops to 30mg / g. The temperature is controlled at 155°C, 0.01g of hydroquinone is added, the temperature is controlled at 95°C, 50g of styrene is added, stirred evenly and cooled to obtain a modified unsaturated polyester.
[0075] Comparative Example 7 The preparation method of the modified unsaturated polyester comprises the following steps:
[0076] S1: In a nitrogen atmosphere, 100 g of dicyclopentadiene, 102 g of maleic anhydride, 28 g of diethylene glycol, and 0.4 g of phosphoric acid were added to a reactor with a reflux device and dispersed evenly, the temperature was controlled at 105°C, and the reaction was kept warm for 0.5 h. 17 mL of deionized water was added, the temperature was controlled at 125°C, and the reaction was kept warm for 3 h to obtain a reaction solution;
[0077] S2: In a nitrogen atmosphere, 100 g of reaction solution, 35 g of phthalic anhydride, 5.5 g of diethylene glycol, 25.2 g of 1,2-propylene glycol, and 0.01 g of hydroquinone are added to a reactor with a distillation device and dispersed evenly. The temperature is first raised to 155°C and kept warm for 2 hours; then the temperature is raised to 165°C and kept warm for 0.5 hours; finally the temperature is raised to 180°C and reacted until the acid value drops to 70 mg / g, 15 g of castor oil is added, the temperature is controlled at 195°C, and the reaction is kept warm until the acid value drops to 30 mg / g, the temperature is controlled at 155°C, 0.01 g of hydroquinone is added, the temperature is controlled at 95°C, 50 g of styrene is added, stirred evenly and cooled to obtain a modified unsaturated polyester.
[0078] Comparative Example 8 A method for preparing composite putty for repairing the surface of a steel structure comprises the following steps:
[0079] B1: 50g of the modified unsaturated polyester prepared in Comparative Example 4, 0.5g of cobalt cyclohexaneate, 1.5g of dimethylaniline, 1g of fumed silica, 35g of talc, 3g of barium sulfate, and 2g of titanium dioxide were mixed evenly, and vacuumed to obtain a main agent;
[0080] B2: 6 g of cyclohexanone peroxide, 3.9 g of dibutyl phthalate, and 0.1 g of white carbon black were blended to obtain a curing agent;
[0081] B3: Mix 50g of the main agent and 1g of the curing agent to obtain putty.
[0082] Comparative Example 9 A method for preparing composite putty for repairing the surface of a steel structure comprises the following steps:
[0083] B1: 50g of the modified unsaturated polyester prepared in Comparative Example 5, 0.5g of cobalt cyclohexaneate, 1.5g of dimethylaniline, 1g of fumed silica, 35g of talc, 3g of barium sulfate, and 2g of titanium dioxide were mixed evenly, and vacuumed to obtain a main agent;
[0084] B2: 6 g of cyclohexanone peroxide, 3.9 g of dibutyl phthalate, and 0.1 g of white carbon black were blended to obtain a curing agent;
[0085] B3: Mix 50g of the main agent and 1g of the curing agent to obtain putty.
[0086] Comparative Example 10 A method for preparing composite putty for repairing the surface of a steel structure comprises the following steps:
[0087] B1: 50g of the modified unsaturated polyester prepared in Comparative Example 6, 0.5g of cobalt cyclohexaneate, 1.5g of dimethylaniline, 1g of fumed silica, 35g of talc, 3g of barium sulfate, and 2g of titanium dioxide were stirred evenly, and vacuumed to obtain a main agent;
[0088] B2: 6 g of cyclohexanone peroxide, 3.9 g of dibutyl phthalate, and 0.1 g of white carbon black were blended to obtain a curing agent;
[0089] B3: Mix 50g of the main agent and 1g of the curing agent to obtain putty.
[0090] Comparative Example 11 A method for preparing composite putty for repairing the surface of a steel structure comprises the following steps:
[0091] B1: 50g of the modified unsaturated polyester prepared in Comparative Example 7, 0.5g of cobalt cyclohexaneate, 1.5g of dimethylaniline, 1g of fumed silica, 35g of talc, 3g of barium sulfate, and 2g of titanium dioxide were mixed evenly, and vacuumed to obtain a main agent;
[0092] B2: 6 g of cyclohexanone peroxide, 3.9 g of dibutyl phthalate, and 0.1 g of white carbon black were blended to obtain a curing agent;
[0093] B3: Mix 50g of the main agent and 1g of the curing agent to obtain putty.
[0094] Performance Testing
[0095] (1) Adhesion: The test was conducted according to GB / T 1720-2020 “Determination of adhesion of paint films”. The test results are shown in Table 1.
[0096] (2) Impact resistance: tested according to GB / T 1732-2020 “Determination of impact resistance of paint films”. The test results are shown in Table 1.
[0097] (3) Flexibility: Tested according to GB / T 1748-1979 “Test method for flexibility of putty film”. The test results are shown in Table 1.
[0098] (4) Sandable time: At 25°C, start timing from the time the main agent and curing agent are mixed and stop timing when the sandpaper does not stick when sanded. This is the sandable time To of the putty. The test results are shown in Table 1.
[0099] Table 1: Mechanical properties test of paint films of Examples 5-7 and Comparative Examples 8-11
[0100]
[0101] It can be seen from Table 1 that the putty prepared in the present application has strong adhesion, excellent polishability, and good flexibility and impact resistance.
[0102] (4) Nitrolacquer resistance: Spray nitroacrylic enamel paint on the polished putty surface and observe the surface condition of the paint film. The test results are shown in Table 2.
[0103] (5) Moisture and heat resistance: Tested according to GB / T 1740-2007 “Determination of moisture and heat resistance of paint films”. The test results are shown in Table 2.
[0104] (6) Salt resistance: Tested according to GB / T 1763-1979 “Determination of resistance of paint films to chemical agents”. The test results are shown in Table 2.
[0105] (7) Gasoline resistance: The test was conducted in accordance with GB / T 1734-1993 “Determination of gasoline resistance of paint films”. The test results are shown in Table 2.
[0106] Table 2: Paint film performance test of Examples 5-7 and Comparative Examples 8-11
[0107]
[0108] It can be seen from Table 2 that the putty prepared in this application has good corrosion resistance.
[0109] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing composite putty for surface repair of steel structure parts, characterized in that: The method comprises the following steps: mixing a main agent and a curing agent to obtain putty; The main agent comprises the following raw materials in parts by weight: 40-50 parts of modified unsaturated polyester, 1-3 parts of accelerator, 1-2 parts of fumed silica, and 40-50 parts of filler; The preparation method of the modified unsaturated polyester comprises the following steps: S1: In a nitrogen atmosphere, dicyclopentadiene, maleic anhydride, diethylene glycol and phosphoric acid are added to a reaction kettle with a reflux device and dispersed evenly, the temperature is controlled at 100-110°C, and the reaction is kept warm for 0.5-1h, deionized water is added, the temperature is controlled at 120-130°C, and the reaction is kept warm for 2-4h to obtain a reaction solution; S2: In a nitrogen atmosphere, the reaction liquid, phthalic anhydride, diethylene glycol, 1,2-propylene glycol, and hydroquinone component 1 are added to a reactor with a distillation device and dispersed evenly, and a three-stage temperature increase reaction is carried out until the acid value drops to 60-70 mg / g, an additive is added, the temperature is controlled at 190-200°C, and the temperature is kept to react until the acid value drops to 30-40 mg / g, the temperature is controlled at 150-160°C, and the hydroquinone component 2 is added, the temperature is controlled at 90-100°C, styrene is added, stirred evenly, and cooled to obtain a modified unsaturated polyester; The additive is obtained by esterifying castor oil with maleic anhydride and then reacting with gamma-aminopropyltriethoxysilane.
2. The method for preparing composite putty for surface repair of steel structure parts according to claim 1, characterized in that: The addition ratio of dicyclopentadiene, maleic anhydride, diethylene glycol, phosphoric acid and deionized water in S1 is 100 g: 92-122 g: 24-32 g: 0.4-0.5 g: 15-20 mL.
3. The method for preparing composite putty for surface repair of steel structure parts according to claim 1, characterized in that: In S2, hydroquinone component one and hydroquinone component two are both hydroquinone; the addition ratio of reaction solution, phthalic anhydride, diethylene glycol, 1,2-propylene glycol, hydroquinone component one, admixture, hydroquinone component two and styrene is 100g: 30-40g: 3.5-7g: 20.2-27.8g: 0.01-0.02g: 10-15g: 0.01-0.02g: 45-55g.
4. The method for preparing composite putty for surface repair of steel structure parts according to claim 1, characterized in that: The preparation method of the admixture comprises the following steps: A1: Add castor oil and maleic anhydride into reactor A and disperse them evenly. Control the temperature at 100-110°C and keep the temperature for 3-6 hours to obtain carboxylated castor oil. A2: Add carboxylated castor oil, γ-aminopropyltriethoxysilane and triethylamine into reactor B and disperse them evenly. Control the temperature at 70-80°C and keep the temperature for reaction for 1-3 hours to obtain an admixture.
5. The method for preparing composite putty for surface repair of steel structure parts according to claim 1, characterized in that: The specific procedure of the three-stage temperature increase reaction in S2 is: first increase the temperature to 150-160°C and keep warm for 1-3 hours; then increase the temperature to 165-170°C and keep warm for 0.5-1 hour; finally increase the temperature to 175-185°C and react until the acid value drops to 60-70 mg / g.
6. The method for preparing composite putty for surface repair of steel structure parts according to claim 1, characterized in that: The polymerization inhibitor is at least one of hydroquinone and p-tert-butylquinone; The accelerator is obtained by mixing a cobalt drier and dimethylaniline in a mass ratio of 0.1-0.5:1.5-2.5, wherein the cobalt drier is cobalt cyclohexaneate or cobalt isooctanoate; The filler is obtained by mixing talcum powder, barium sulfate and titanium dioxide in a mass ratio of 35-45:1-10:2-5.
7. The method for preparing composite putty for surface repair of steel structure parts according to claim 1, characterized in that: The mass ratio of the main agent to the curing agent in the putty is 100:2-3.
8. The method for preparing composite putty for surface repair of steel structure parts according to claim 1, characterized in that: The curing agent comprises the following raw materials in percentage by weight: 50-60% peroxide initiator, 30-49% plasticizer, 1% pigment, and the sum of the percentages of the raw materials is 100%.
9. The method for preparing composite putty for surface repair of steel structure parts according to claim 8, characterized in that: The plasticizer is any one of a diformic acid ester plasticizer, a polyester plasticizer, a phosphate ester plasticizer, a fatty acid ester plasticizer, and an epoxy ester plasticizer; The peroxide is any one of cumene hydroperoxide, di-tert-butyl peroxide, dicumyl peroxide, benzoyl peroxide, dilauroyl peroxide, cyclohexanone peroxide, and methyl ethyl ketone peroxide; The pigment is at least one of an organic pigment and an inorganic pigment.
10. A composite putty for repairing the surface of a steel structure, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Patent Citations
High-speed rail putty polyester resin material, main agent, preparation methods of high-speed rail putty polyester resin material and main agent, high-speed rail putty and application method of high-speed rail putty
CN113061241A